To die in Mexico: dispatches from inside the drug war - Gibler, John (Open media series, 2011)
Since President Calderón declared a war on drugs in December 2006, more than 38,000 Mexicans have been murdered. Drug money is now Mexico's single largest source of income. Gibler travels across Mexico and slips behind the frontlines to talk with people who live in towns under assault on the lawless frontiers of the drug war